2014
DOI: 10.1186/1471-2474-15-162
|View full text |Cite
|
Sign up to set email alerts
|

Population prevalence of ultrasound features of osteoarthritis in the hand, knee and hip at age 63 years: the Newcastle thousand families birth cohort

Abstract: BackgroundMusculoskeletal ultrasound has been found to be more sensitive than radiographs in detecting osteophytes. Our objective was to measure the prevalence of features of osteoarthritis (OA), in the dominant hand, knees and hips using ultrasound, within the Newcastle Thousand Families birth cohort.MethodsParticipants were aged 61–63 (mean 63) years. Knee images were scored for presence of osteophytes and effusion. Hip images were scored for the presence of osteophytes and femoral head abnormality. The firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 38 publications
(49 reference statements)
4
42
0
3
Order By: Relevance
“…Ultrasound evidence of generalised OA (48%) and isolated hand OA (31%) was common, compared to isolated hip or knee OA (5%) and both hip and knee OA (3%). The higher prevalence of hand and hip OA observed in this study compared with previous radiographic studies, supports the hypothesis that ultrasound is more sensitive than radiography in detecting OA, particularly for osteophytes 14 . Further work will be needed to determine its role in clinical settings and epidemiological studies.…”
Section: New Lessons From Ultrasoundsupporting
confidence: 86%
See 2 more Smart Citations
“…Ultrasound evidence of generalised OA (48%) and isolated hand OA (31%) was common, compared to isolated hip or knee OA (5%) and both hip and knee OA (3%). The higher prevalence of hand and hip OA observed in this study compared with previous radiographic studies, supports the hypothesis that ultrasound is more sensitive than radiography in detecting OA, particularly for osteophytes 14 . Further work will be needed to determine its role in clinical settings and epidemiological studies.…”
Section: New Lessons From Ultrasoundsupporting
confidence: 86%
“…Baseline ultrasound detected gray-scale synovitis and power Doppler signals predicted radiographic progression of hand OA after 5 years 62 . Another study showed that ultrasound detected inflammatory features, including synovial thickening, effusion and power Doppler signal, especially when persistently 3 Radiography Hip and pelvic geometry are associated with the risk of compartment-specific knee OA Thomas GE, et al 49 Radiography Cam-type FAI and acetabular dysplasia predict development of hip OA and joint replacement High bone mineral density is associated with knee and hip OA Hardcastle SA, et al 4e6 Radiography High BMD Z scores are associated with increased prevalence of hip and knee OA, specifically osteophytosis Potential new approaches to examining joint structures Turunen M, et al 7 CT CBCT can measure volumetric BMD of cortical, trabecular, and subchondral trabecular bone Kokkonen HT, et al 8 CT Arthrographic images enables sensitive detection of cartilage lesions Riecke BF, et al 10 US Ultrasound score is reliable and valid in detecting knee OA Abraham AM, et al 14 US US demonstrates higher prevalence of osteophytes in hand and hip OA than radiographic studies Liukkonen J, et al 15 US Arthroscopic ultrasound imaging quantitatively evaluates articular cartilage Hirata Y, et al 16 Kobayashi N, et al 17 PET 18F-fluoride uptake is associated with mechanical stress in hip OA and can detect bone abnormalities earlier than MRI Ultrasonographic abnormalities correlate with clinical endpoints Hall M, et al 11 US Effusion and synovial hypertrophy are more common in knee OA, with severity correlating with radiographic severity of knee OA Birn J, et al 12 US Large joint effusions correlates with rapidly destructive hip OA Malas FU, et al 13 US Meniscal bulging is associated with radiographic joint space narrowing and KL grades What is new in magnetic resonance imaging? Morphological structural abnormalities predict clinical endpoints Sharma L, et al 19 MRI Cartilage damage, BMLs, meniscal tears, and meniscal extrusion are associated with prevalent frequent knee symptoms and/or incident persistent symptoms Roemer FW, et al 21 MRI Cartilage damage, BMLs, meniscal damage, synovitis and effusion predicted short-term need for knee joint replacement Eckstein F, et al 22 MRI Accelerated cartilage thickness loss is greatest closest to the time of knee replacement Composition of cartilage influences morphometry Crema MD, et al 25 MRI Poorer dermis endpoints are associated with increased cartilage thickness, potentially representing "cartilage swelling" Ukiah T, et al 26 MRI Diffusion tensor imaging can distinguish early cartilage damage Wyatt C, et al …”
Section: Mri and Ultrasound Findings Predict Progression Of Hand Oa Amentioning
confidence: 99%
See 1 more Smart Citation
“…In the Framingham Osteoarthritis Study, the age-standardized prevalence of radiographic hip OA was 19.6%; prevalence of radiographic (but not symptomatic) hip OA was higher in men (135). The prevalence of OA features by ultrasound was described in participants from the Newcastle thousand families birth cohort (136). In a large sample of residents of Malmö, Sweden, 25% had radiographic knee OA and 15% had either symptomatic or clinically defined knee OA (137).…”
Section: Resultsmentioning
confidence: 99%
“…To date, scoring of photographic images for OA using the AGES-Reykjavik scoring system has been limited to researchers who developed the atlas, further testing the reliability and validity should be undertaken by other investigators. Additionally, the longitudinal validity of a photographic grading system was compared to radiographic imaging which is known to be not as sensitive as ultrasound and MRI [23,24] and does not allow the visualisation of the full range of joint tissues affected by hand OA [25][26][27][28]. Therefore other imaging methods, although more expensive and less feasible in large population-based studies, may have been more sensitive in determining structural change against which photographic change could have been compared.…”
Section: Discussionmentioning
confidence: 99%